New Energy Wide Area Complementary Planning Method for Multi-Energy Power System - Xun Suo (IEEE, 2021)
Vigorously developing new energy is an important measure to deal with the energy crisis and environmental degradation, but the volatility and randomness of its output have brought great challenges to the new energy consumption. In this paper, the maximum new energy consumption is taken as the objective function, and the power flow constraints, multi-energy source capacity constraints and electrical constraints are taken as the constraints. Based on the complex adaptive system theory, the minimum construction step size of new energy sources is taken as the agent for modeling, focusing on the coordination among multiple sources, adjusting the installed node position and capacities of various types of power sources to obtain the optimal layout of power sources for multi-energy power systems. Based on the actual meteorological and operational data of a regional power grid in Northwest China, the original power system is re-planned. The simulation results verify the effectiveness of the proposed planning method.